#TITLE_ALTERNATIVE# - Heri Soelityo Utomo (NIM 201 00 008), Robertus
Abstract : This paper considers the mixed-norm H2 / H00 standard problem. Specifically, an LQG control design problem involving a constraint on H disturbance attenuation is addressed. It is shown that the H, / H00 mixed compensator gains are completely characterized via coupled Riccati / Lyapunov equation. The principal result involves sufficient condition for characterizing full order controllers guarenteeing closed loop stability, constrained H00 disturbance attenuation and an optimized H2 performance bound.